The Role of Organizational Commitment in Improving Performance: A Qualitative Case Study at The Indonesian Ministry of Manpower - Dini, Rifki; Dwi Putri Pramesti, Ginna Novarianti; Amelia, Amelia (Institut Manajemen Wiyata Indonesia, 2025)
This study aims to analyze the role of organizational commitment in improving employee performance at the Indonesian Ministry of Manpower. The approach employed is qualitative, utilizing a case study method that involves interviews, questionnaires, and observations. The study's results indicate that organizational commitment has a significant impact on employee performance. Supportive leadership, career development facilities, and rewards for performance have proven to be key factors in strengthening employee commitment. Employees who feel valued and have opportunities to grow tend to perform better. However, despite the generally high level of commitment, the results of the questionnaire indicate that career development facilities still require improvement. This study suggests that the Indonesian Ministry of Manpower should strengthen its human resource development policies, particularly in terms of training and performance awards, to maintain and enhance employee commitment and performance. These findings contribute to human resource management in the government sector and provide the basis for further research in a broader context.